2021
DOI: 10.1001/jamacardio.2021.2312
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitral Annular Disjunction With Cardiovascular Outcomes Among Patients With Marfan Syndrome

Abstract: IMPORTANCE Mitral annular disjunction (MAD) has received particular interest in patients with mitral valve prolapse, ventricular tachycardia, and sudden cardiac death. The clinical significance of MAD for patients with Marfan syndrome (MFS) remains largely unexplored. OBJECTIVE To define the prevalence of MAD and examine its association with cardiovascular outcomes and arrhythmia among patients with MFS. DESIGN, SETTING, AND PARTICIPANTS This retrospective, single-center cohort study included 142 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…56 Another recent article reported that 34% of 142 patients with Marfan syndrome had MAD as diagnosed by TTE. 57 Patients with MAD had larger aortic root z scores and more MVP, ventricular ectopy, and NSVT. This association between MAD and genetic connective tissue disorders raises the question of related causative mechanisms and warrants further investigation.…”
Section: Mad In Special Populationsmentioning
confidence: 91%
“…56 Another recent article reported that 34% of 142 patients with Marfan syndrome had MAD as diagnosed by TTE. 57 Patients with MAD had larger aortic root z scores and more MVP, ventricular ectopy, and NSVT. This association between MAD and genetic connective tissue disorders raises the question of related causative mechanisms and warrants further investigation.…”
Section: Mad In Special Populationsmentioning
confidence: 91%
“…disease including more arrhythmic events, a higher need for mitral valve intervention, and among patients with extensive MAD, more arrhythmic events. 66,67 The first large prospective cohort of isolated MVP with systematic MAD assessment reported a prevalence of 30% of MAD, generally in younger patients. 15 Advanced myxomatous-degeneration, denoted by marked leaflet-redundancy and bileaflet-MVP, was the strongest MAD-associated MVP feature.…”
Section: Box 1 Summary Of Diagnostic Criteria For Madmentioning
confidence: 99%
“…In an animal model with MFS, the increased TGF-β activity and signalling has been shown to correlate temporally and spatially with mitral valve pathology. 5 Demolder et al 33 described a 34% prevalence of MAD in MFS patients which was associated with the occurrence of arrhythmic events, a higher need for mitral valve intervention and increased aortic events in the form of dissection and prophylactic aortic surgery for dilatation. Chivulescu et al 34 reported a 41% prevalence of MAD in a combined cohort of MFS and Loeys-Dietz syndrome patients, associated with a more severe disease phenotype characterized by aortic surgery at younger age and frequent need for mitral surgery.…”
Section: Discussionmentioning
confidence: 99%